Development of Articulate Storyline Learning Media for Pancasila Education Subjects to Increase Student Learning Interest - Sunaryati, Titin Sunaryati (Attadib: Journal of Elementary Education, 2023)
AbstractThe decline in student interest in learning is partly due to the limited use of learning media during the learning process and teachers who have not been able to utilise technology to be used as learning media. The purpose of the study was to produce Artiqulate Storyline learning media for Pancasila Education subjects to increase the learning interest of grade V elementary school students. The research method uses R&D with the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The subjects of this research were 26 students, as well as involving media experts, material experts. Data collection techniques were carried out by observation, interviews and questionnaires. The data analysis used is descriptive and categorical analysis to see the feasibility of the developed media. The results showed that the learning media developed was feasible to be used by students and helped teachers in the learning process, it can be seen from the results of media expert validation of 95%, material experts of 97.5% with a feasible category. Student learning interest increases when learning using Artiqulate Storyline learning media, it can be seen from the results of the N-Gain Test of 0.6 in the high category